Acceptance and Commitment Therapy as a Treatment for Scrupulosity in Obsessive Compulsive Disorder. (May 2013) - Dehlin, John P.; Morrison, Kate L.; Twohig, Michael P.
This study evaluated acceptance and commitment therapy (ACT) for scrupulosity-based obsessive compulsive disorder (OCD). Five adults were treated with eight sessions of ACT, without in-session exposure, in a multiple baseline across participants design. Daily monitoring of compulsions and avoided valued activities were tracked throughout the study. The Obsessive Compulsive Inventory–Revised, Yale–Brown Obsessive Compulsive Scale (Y-BOCS), Penn Inventory of Scrupulosity, Beck Depression Inventory–II, Quality of Life Scale, Santa Clara Strength of Religious Faith Questionnaire, and the Acceptance and Action Questionnaire–II were completed at pretreatment, posttreatment, and 3-month follow-up. The Treatment Evaluation Inventory was completed at posttreatment. Average daily compulsions reduced as follows: pretreatment = 25.0, posttreatment = 5.6, and follow-up = 4.3. Average daily avoided valued activities reduced as follows: pretreatment = 6.0, posttreatment = 0.7, and follow-up = 0.5. Other measures showed similar patterns. Religious faith only slightly declined: 4% at posttreatment and 7% at follow-up. Treatment acceptability was high.